Pengaturan Jadwal Distribusi Minyak Goreng dengan Metode Distribution Requirement Planning (Studi Kasus: CV. Berkah Sumber Abadi) - , Khoirul Yanuar Rizky; Herlina (Jurnal Serambi Engineering, 2025)
CV. Berkah Sumber Abadi is one of the distribution companies in East Java that focuses on the distribution of packaged edible oil. The application of CV. Berkah Sumber Abadi's distribution system uses one-time delivery after receiving an order from a customer. This system resulted in the distribution costs incurred by CV. Berkah Sumber Abadi to be quite high. To overcome this, an analysis is needed using the Distribution Requirement Planning (DRP) method, which is useful for minimising distribution costs, so that the company can rationalise distribution costs. The lot size calculation method using Silver Meal is applied to optimise effective and efficient order lot sizes. The results showed that the Distribution Requirement Planning (DRP) method was able to significantly reduce distribution costs by planning a more regular delivery schedule. In addition, the Silver Meal method successfully reduces inventory costs by determining the optimal lot size according to the demand of each period. With the Distribution Requirement Planning (DRP) method, the distribution cost of Fermina cooking oil products was reduced by 22% compared to the system used by CV. Source: Berkah Abadi. The total distribution cost using the enterprise method was Rp 68,760,000, while using the Distribution Requirement Planning (DRP) method was Rp 53,500,000.